Synchrotron X-ray footprinting on tour - Bohon, Jen (International Union of Crystallography, 2014)
Synchrotron footprinting is a valuable technique in structural biology for understanding macromolecular solution-state structure and dynamics of proteins and nucleic acids. Although an extremely powerful tool, there is currently only a single facility in the USA, the X28C beamline at the National Synchrotron Light Source (NSLS), dedicated to providing infrastructure, technology development and support for these studies. The high flux density of the focused white beam and variety of specialized exposure environments available at X28C enables footprinting of highly complex biological systems; however, it is likely that a significant fraction of interesting experiments could be performed at unspecialized facilities. In an effort to investigate the viability of a beamline-flexible footprinting program, a standard sample was taken on tour around the nation to be exposed at several US synchrotrons. This work describes how a relatively simple and transportable apparatus can allow beamlines at the NSLS, CHESS, APS and ALS to be used for synchrotron footprinting in a general user mode that can provide useful results.